Recent progress in the application of chromatography-coupled mass-spectrometry in the analysis of contaminants in food products - Zhuzi Chen; Zamar Daka; Liying Yao; Jiamin Dong; Yuqi Zhang; Peiqi Li; Kaidi Zhang; Shunli Ji (Food Chemistry: X)
An increasing concern has marked the past few years for food quality and safety, not only by the research community but also among the general public. Due to the increasing prevalence of emerging contaminants/analogues in various food matrices, significant efforts have been focused on developing green extraction, matrix preparation, multi-targeted, and potentially multi-matrix techniques that minimize waste generation, cost, and the use of organic reagents to optimize recyclability throughout the analytical procedure. This, therefore, not only guarantees consumer protection through food safety but also contributes to progress in green analysis, ultimately preventing the one-step forward and two-steps back phenomenon of ensuring food safety while damaging the environment. In this review, we provide an integrated, concise, and comprehensive timeline of the research endeavours in the application of chromatography coupled with mass spectrometry in the analysis of contaminants in plant-, aquatic-, and animal-derived food matrices.